An integrated inventory location model considering all-unit quantity discount - Tang, Sai Hong; Firoozi, Zahra; Mohd Ariffin, Mohd Khairol Anuar; Ariafar, Shahram (Academic Journals, 2011)
One of the recent areas in distribution network design is integrated inventory location problems, which jointly determines the inventory control decisions and facility location decisions of a distribution network. A typical distribution network consists of suppliers, several retailers, and several distribution centers. Distribution centers order products from suppliers to fulfil demands of retailers. To achieve risk pooling benefits, inventory of several retailers is aggregated into one distribution center. This situation has made distribution centers more likely to take the advantage of quantity discount from suppliers. However, most previous models have investigated the problem under the basic economic order quantity EOQ with (Q, r) inventory policy and yet quantity discount has not been considered. This paper shows that considering quantity discount instead of EOQ policy can reduce the total cost and change the optimal configuration of the networks.